Impact of polar ice sheet destabilisation on climate and vector-borne disease risk during the 21st century - (:unkn) unknown (My University, 2023)
Mosquitoes, major vectors of diseases, are sensitive to rainfall which is necessary for their immature aquatic stages, and to temperature which affects their development and life cycle dynamics. Climate change can therefore impact the transmission of vector-borne diseases such as malaria, the world's major parasitic disease causing over 600,000 deaths per year, and Rift Valley Fever (RVF), a zoonotic disease decimating herds, causing health risks and catastrophic economic losses in Africa.The Intergovernmental Panel on Climate Change (IPCC) report provides climate scenarios for the 21st century with different standard greenhouse gas emission scenarios, named Representative Concentration Pathway (RCP). By 2080, the risk of malaria transmission is estimated to decrease in the Sahel region and to increase in the East African Plateau as a result of rising temperatures under the RCP8.5 scenario. Although paleoclimate studies show that melting ice sheet can induce abrupt climate change, state of the art IPCC future projections do not consider such a potential rapid destabilisation of polar ice sheets. However, the West Antarctic and Greenland ice sheet are vulnerable to climate change and even a partial melting would cause major climatic changes, even in tropical regions. No study has yet quantified the impact of an abrupt melting of the ice sheets on the distribution of malaria and RVF. This work is based on future climate numerical simulations using the coupled global climate model IPSL-CM5A-LR with RCP8.5 as radiative forcing. Simulations of freshwater release, corresponding to the accelerated and partial melting of the polar ice sheets, were carried out with different melting assumptions:-for Greenland, a freshwater flux equivalent to a global sea level rise of 0.5m, 1m, 1.5m and 3m is released into the North Atlantic;-for Antarctica, a quantity of freshwater equivalent to a global sea level rise of 3m is released off its western part.These continuous wa
Keywords: African Research